Creation of a novel zebrafish model with low DHA status to study the role of maternal nutrition during neurodevelopment - Katherine M. Ranard; Bruce Appel (Journal of Lipid Research)
Docosahexaenoic acid (DHA), a dietary omega-3 fatty acid, is a major building block of brain cell membranes. Offspring rely on maternal DHA transfer to meet their neurodevelopmental needs, but DHA sources are lacking in the American diet. Low DHA status is linked to altered immune responses, white matter defects, impaired vision, and an increased risk of psychiatric disorders during development. However, the underlying cellular mechanisms involved are largely unknown, and advancements in the field have been limited by the existing tools and animal models. Zebrafish are an excellent model for studying neurodevelopmental mechanisms. Embryos undergo rapid external development and are optically transparent, enabling direct observation of individual cells and dynamic cell-cell interactions in a way that is not possible in rodents. Here, we create a novel DHA-deficient zebrafish model by 1) disrupting elovl2, a key gene in the DHA biosynthesis pathway, via CRISPR/Cas9 genome editing, and 2) feeding mothers a DHA-deficient diet. We show that low DHA status during development is associated with an abnormal eye phenotype and demonstrate that even morphologically normal siblings exhibit dysregulated vision and stress response gene pathways. Future work using our zebrafish model could reveal the cellular and molecular mechanisms by which low DHA status leads to neurodevelopmental abnormalities, and provide insight into maternal nutritional strategies that optimize infant brain health.